2015
DOI: 10.3897/bdj.3.e4078
|View full text |Cite
|
Sign up to set email alerts
|

PASSIFOR: A reference library of DNA barcodes for French saproxylic beetles (Insecta, Coleoptera)

Abstract: Saproxylic beetles – associated with dead wood or with other insects, fungi and microorganisms that decompose it – play a major role in forest nutrient cycling. They are important ecosystem service providers and are used as key bio-indicators of old-growth forests. In France alone, where the present study took place, there are about 2500 species distributed within 71 families. This high diversity represents a major challenge for specimen sorting and identification.The PASSIFOR project aims at developing a DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
6
18
0
Order By: Relevance
“…DNA barcoding has a strong track record in delivering species-level identifications for the five insect orders with the most pest species-Coleoptera (Woodcock et al 2013;Rougerie et al 2015), Diptera (Nagy et al 2013;Smit et al 2013), Hemiptera (Park et al 2011b;Raupach et al 2014), Lepidoptera (Janzen et al 2005;Ashfaq et al 2013), and Thysanoptera (Rebijith et al 2014;Iftikhar et al 2016). For example, 92.2% of 3514 species of European beetles were assigned to a distinct BIN that coincided with a known morphological species, while most of the other species were assigned to two or three BINs, suggesting they represent cryptic species complexes (Hendrich et al 2015).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…DNA barcoding has a strong track record in delivering species-level identifications for the five insect orders with the most pest species-Coleoptera (Woodcock et al 2013;Rougerie et al 2015), Diptera (Nagy et al 2013;Smit et al 2013), Hemiptera (Park et al 2011b;Raupach et al 2014), Lepidoptera (Janzen et al 2005;Ashfaq et al 2013), and Thysanoptera (Rebijith et al 2014;Iftikhar et al 2016). For example, 92.2% of 3514 species of European beetles were assigned to a distinct BIN that coincided with a known morphological species, while most of the other species were assigned to two or three BINs, suggesting they represent cryptic species complexes (Hendrich et al 2015).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…The beetle fauna of North and Central Europe has recently been DNA barcoded extensively (Pentinsaari et al 2014;Hendrich et al 2015;Rougerie et al 2015). These barcode reference libraries provide an efficient tool for the detection of adventive European beetle species in other parts of the world, particularly for those taxonomic groups where the native fauna is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade due to intensive barcoding of European Coleoptera it was revealed that A. reyi does not diff er from A. dubia by the molecular signs of cytochrome c oxidase I (COI) (Rougerie et al, 2015;Hendrich et al, 2015;Wu et al, 2016). Moreover, Hendrich et al (2015) noted that all sequenced specimens of both species were not grouped in separated clades on their phylogenetic trees; instead, they are completely mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hendrich et al (2015) noted that all sequenced specimens of both species were not grouped in separated clades on their phylogenetic trees; instead, they are completely mixed. Rougerie et al (2015) assumed possibility of the past or current hybridization between A. reyi and A. dubia. Th ey also supposed continuing speciation with low divergence of both species.…”
Section: Introductionmentioning
confidence: 99%